Developing Electronic Student Worksheets Based on Ethnoscience to Train Smart Risk-Taking Behaviour and Growth Mindset - Viyanti, Viyanti; Sunyono, Sunyono; Rosdiana, Tjaturningsih; Anggreini, Anggreini; Jarwadi, Jarwadi; Priowicaksono, Noorman (Jurnal Pendidikan MIPA, 2024)
Abstract: This study aims to determine the practicality and effectiveness of electronic student worksheets based on ethnoscience in training smart risk-taking behavior and a growth mindset. The research employed a hybrid type III mixed-method with a sequential explanatory design, combining quantitative and qualitative approaches. The subjects of the study were junior high school students in Lampung Province, selected randomly. The worksheets were developed based on ethnoscience principles, integrating local culture, traditional knowledge, and scientific knowledge, with validity tested by experts. Quantitative data were collected through product validity tests and hypothesis testing, while qualitative data were gathered through interviews and observations. Quantitative analysis showed a validity score of 91.60% with very high criteria, and hypothesis testing indicated significant differences between the experimental and control classes in the ability to exhibit smart risk-taking behavior and a growth mindset. Based on these results, it is concluded that ethnoscience-based worksheets are effective in training smart risk-taking behavior and a growth mindset, emphasizing the importance of integrating local cultural context in educational tools to enhance learning outcomes and personal development. This approach helps bridge the gap between traditional knowledge and modern scientific understanding, creating a more holistic educational framework.         Keywords: electronic student worksheets, ethnoscience, growth mindset, smart risk-taking behavior.DOI: https://doi.org/10.23960/jpmipa/v25i1.pp127-141